FORMULATION AND QUALITY EVALUATION OF THE PREPARATION OF COMBINATION OF TOOTHPASTE BAY LEAF EXTRACT (Syzygium polyanthum) AND MINT LEAVES EXTRACT (Coleus amboinicus L.) - Pramita Yuli Pratiwi; Tiara Puspita Nirmalasari; Achmad Ridlo (Jurnal Jamu Kusuma, 2023)
The content of flavonoid compounds, tannins, and saponins in bay leaves acts as an antibacterial. In addition, the content of terpenoid compounds, namely menthol compounds found in mint leaves have antibacterial activity. The purpose of this study was to determine the formulation of the method of making toothpaste preparations and the results of the evaluation of the physical quality and phytochemical screening tests on toothpaste preparations. This study made 3 formulas with different variations, namely formula I (F1) bay leaf extract as much as 3 g, formula II (F2) as much as 4.5 g, and formula III (F3) as much as 6 g. This type of research is experimental. The extraction method used is maceration. Quality evaluation carried out included organoleptic tests, pH, homogeneity, foaming power, and spreadability. The results of the three formulas showed that the organoleptic observations were in the form of a paste, had a distinctive aroma and brown color, the pH value was 7, formulas I and II were homogeneous but formula III was not homogeneous, the average spreadability was 5 cm, and the average foam power was 4 cm. The results of the phytochemical screening test for toothpaste preparations with a combination of bay leaf and mint leaf extracts were positive for flavonoids, saponins, and tannins.